Accumulation of mercury in sea bass from a contaminated lagoon (Ria de Aveiro, Portugal) - Abreu, S. N. (2000)
This work reports the distribution of total mercury (Hg) in Dicentrarchus labrax (sea bass) and in material collected in plankton nets from an inner basin contaminated with the effluent from a chlor-alkali plant, and in other locations of a coastal lagoon (Ria de Aveiro, Portugal). Mercury concentrations were higher in material collected in 200 than in 63 μm mesh net. Mercury in seston decreased pronouncedly with the distance to the industrial source (1.3–0.015 μg g−1 on a wet weight basis), and was higher at low tide than at high tide. This indicates that mercury is exported from the contaminated basin through the first levels of the estuarine chain. Mercury was analysed in muscle, liver, gills and stomach content of sea bass. Specimens captured in the contaminated basin showed higher accumulation of mercury: levels in muscle and liver of young specimens exceeded 1 μg g−1 and 2 μg g−1, respectively; gills and stomach content also presented higher concentrations. Mercury increased more drastically in liver than in muscle of specimens exposed to high contamination, changing the liver/muscle Hg ratio. Although juveniles exhibited higher concentrations in the contaminated basin than in other areas, there is an age effect on the accumulation of mercury in sea bass at the contaminated basin. Occasionally, intermediate concentrations were found in specimens captured in other areas of the lagoon.